PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT SAMPOERNA AGRO TBK PERIODE 2013-2022 - Humaira, Chairina; Sutiman (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return On Equity at PT Sampoerna Agro Tbk for the 2013-2022 period, both partially and simultaneously. The type of research used is quantitative research, and is descriptive. The data collection technique used is published secondary data, data taken from the official website of PT Sampoerna Agro Tbk for the 2013-2022 period. The data analysis method used in this research is descriptive statistics, classical assumption testing, and also uses simple and multiple linear regression data analysis techniques, correlation coefficient, hypothesis testing (t test and f test), and coefficient of determination. From the results of the t test hypothesis testing, it shows that the Current Ratio (CR) has no significant effect on Return On Equity where the t value is 1.663 < t table value 2.365, with a significance value of 0.140 > 0.05, while the Debt to Equity Ratio (DER) has no significant effect on Return On Equity where the t value is -1.057 < t table value 2.365, with a significance value of 0.325 > 0.05. Simultaneously (F test) Current Ratio (CR) and Debt to Equity Ratio (DER) together have no significant effect on Return On Equity where the Fcount value is 2.843 < Ftable value 4.46 with a significance of 0.125 > 0.05. The coefficient of determination test shows a value of 44.8%, while the remaining 55.2% is influenced by other variables not examined in this research.